Knowledge of Art in Malaysian Contemporary Visual Art - Mohamad Faizuan Mat (Journal of Visual Art and Design, 2017)
Malaysia has a scarcity in the presentation of art knowledge through visual art. Therefore, this study aims to investigate the importance of art knowledge in the field of visual art. In fact, Malaysian contemporary visual artists appear to have insufficient values of intellectualism and lack shared vision. The intention of this study was to reveal the factors in Malaysian visual arts that led to the crisis in art knowledge development. This project uses a qualitative triangulation method in order to reveal similarities from face-to-face interviews and document studies. The analysis was supported by evidence obtained from observation of several art discourses. The findings of this study revealed the importance of world knowledge and perception of art based on critical thinking. In addition, the results of this study also present the awareness of the valuable contributions of art knowledge in visual art. This paper revealed the factors that lead to the unconvincing development of art knowledge, specifically in Malaysia. The importance of art knowledge can be investigated further in order to validate visual art as an intellectual product that communicates knowledge.